COVID-19 in cancer patients: clinical characteristics and outcome: an analysis of the LEOSS registry - Rüthrich, Maria Madeleine; Giessen-Jung, C.; Borgmann, S.; Classen, A. Y.; Dolff, S.; Grüner, B.; Hanses, F.; Isberner, N.; Köhler, P.; Lanznaster, J.; Merle, Uta; Nadalin, S.; et al. (Annals of hematology, 2021)
Since the early SARS-CoV-2 pandemic, cancer patients have been assumed to be at higher risk for severe COVID-19. Here, we present an analysis of cancer patients from the LEOSS (Lean European Open Survey on SARS-CoV-2 Infected Patients) registry to determine whether cancer patients are at higher risk.
Online veröffentlicht: 7. November 2020
Gesehen am 03.05.2024